Qualifying Earth’s Nature to be Able to Face the Latest Developments of the Climate Changes - Armen Ohan (Current Advances in Geography, Environment and Earth Sciences Vol. 2, 2022)
The global warming has several consequences upon the climate changes one of these consequences are melting world’s glaciers, desertification and the high powered hurricanes where these consequences have a severe impact against the civilization and life on Earth, where melting world’s glaciers guides world’s sea level to raise to extreme levels threatens sinking of wide important areas of the Earth via the sea water and the desertification threatens the demise of all kinds of life in green areas by turning it into deserts as well as the high powered hurricanes threatens to represents as big disasters in the urban areas which costs billions dollars yearly, therefore the issue of the climate change become the issue that determines our existence on Earth. It became clear obvious that the climate changes is the issue of increasing the energy in the environment, which increases the speed of chemical and physical reactions and changes paths to the negative effects and results, therefore new and smart ways should be found to handles the high energies in the environment of the Earth and divert the negative paths towards the positive effects and results upon the environment and life. Purpose: Qualify Earth’s nature to reduce the effects of the climate changes upon the environment and life. Methods: Use the same energy resources which causing the global warming and the climate changes to extract drinking water and qualify the nature of the Earth to support the life factors, avoiding to use another energy resources to grant our used the systems the duration their performance, and finally integrating them to be part of landmarks of the nature. Results: Global warming result of the existence of high level of energy in the Earth’s environment leading to increase the speed of the chemical and physical reactions among the materials on the nature, results the unwanted consequences, which leads to the unregulated distribution of the water quantities in the environment of the Earth between the lack in water in some areas which causes desertification and in the meantime increase it in some other areas which causes flooding, this is due to the unregulated in the rates of evaporation and condensation of the water in the nature, therefore adding some extra systems and foundations to the Earth’s environment which already consume the same energy resources which cause climate changes and some another natural energies and forces, considering Physical and chemical properties of materials, finally integrate these new foundations with the landmarks of the nature, may grant the environment the ability to stand strongly in the face of these challenges in order to do their required functions to support life of Earth. Most of the causes of climate changes are due to the industrial emissions, while world’s industry and economy still depending upon the fossil energy resources, therefore it’s not possible to change the recent situation in a blink of an eye, there are some conferences and agreements aiming to reduce the recent rates of the industrial emissions but the adopted programs works in the long term, until it become possible to build a sophisticated industrial base that relies on alternative energy sources, therefore these programs need a several decades, this means that the recent rates of emissions will continue for a long time, and the global warming rates will also continue increasing until further notice, therefore work should be done on another path as well, which is aiming qualify Earth’s nature to be able to face climate changes, considering the challenge global warming one of the constants in our daily life and handle it via our available capabilities, through building foundations depending upon modestly technology to counter these climate changes. For example when we aim to fight the desertification used the systems must already depend upon the same factors that cause the desertification such as high rates of temperatures and the atomic diffusion of the water into the air considering the physical characteristics of the water in its different values of density in its different phases while benefiting of the energies of nature of the heat and the gravity force of Earth, note that as much as the temperature increases the rates of evaporation of water from water surfaces increases as well, resulting the increase the value of humidity in the atmosphere of the Earth, which have the effects upon the rates of raining in the raining seasons resulting floods threatening cities and agricultural areas, therefore making lakes nearby these important areas could guides the flooding water to move to the lower elevation areas to these lakes via effects of gravity force of the Earth may prevent flooding in the inhabitants and agricultural projects areas, also to use these waters later for human and agricultural purposes, especially that flooding areas are suffering of the lack of raining in the rest of seasons and the desertification.